The Existence of Communication Science in Human Life in the Technology Era in Timor-Leste - Araujo, Bernabe De lima (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This research seeks to explore, the development of information technology and digital media has brought about a major change in the way people communicate and interact in society. This research seeks to explore the role of communication science in the lived experience of people in the age of technology. This study uses a qualitative research approach of a descriptive nature, which involves data analysis through the exploration of concepts, theories, and interpretations of communication phenomena in society. The research results show that communication science is a discipline grounded in principles, theories, and concepts that explain the process of human communication. This field analyzes how information is transmitted, received, and interpreted by individuals, groups, organizations, and societies in various social, cultural, and technological contexts. In the Timor-Leste context, the development of digital media such as Facebook, WhatsApp, and other online platforms contributes to changing the dynamics of communication between individuals and institutions. Communication science is not only an academic field, but also a practical skill that has important value in everyday life. Its presence helps people better understand social interactions, improve interpersonal relationships, and interpret the influence of the mass media on the thoughts, behaviors, and perceptions of society. Therefore, communication science plays a fundamental role in the development of modern society, especially in the era of technology where information can be distributed quickly and widely